1993
DOI: 10.1073/pnas.90.9.3918
|View full text |Cite
|
Sign up to set email alerts
|

Histone H1 deposition and histone-DNA interactions in replicating chromatin.

Abstract: An immunochemical method for analyzing protein interactions with BrdUrd-substituted DNA was used to study binding of histones to nascent DNA in nuclei. The results indicate that in Ehrlich ascites tumor (EAT) cells, histone Hi deposits on newly replicated DNA simultaneously with or immediately after core histone deposition so that in chromatin replicated for 3 min, the stoichiometry of the histones is the same as in bulk chromatin. All histones, and especially histone Hi, interact with nascent DNA more weakly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…H1 concentrations and NRL values in those cells rapidly evolve to the values present in mature chromatin [13]. The same behavior was observed in Ehrlich ascites tumor cells (EAT) [14], suggesting a relationship between these factors and certain tumors.…”
Section: Introductionmentioning
confidence: 84%
“…H1 concentrations and NRL values in those cells rapidly evolve to the values present in mature chromatin [13]. The same behavior was observed in Ehrlich ascites tumor cells (EAT) [14], suggesting a relationship between these factors and certain tumors.…”
Section: Introductionmentioning
confidence: 84%
“…Whether this reflects a true reduction in NRL or the high mobility of nascent nucleosomes (Smith et al 1984) is uncertain. However, it is clear that newly replicated chromatin is in a state of rapid flux, and rapidly changes to the mature NRL and H1 content (Annunziato et al 1981, Bavykin et al 1993. Interestingly, in a study of replication in synchronized CHO cells in the presence of hydroxyurea, D' Anna et al (1986) reported that the newly synthesized chromatin had a shortened NRL and was depleted in H1.…”
Section: Nucleosome Repeat Length and H1mentioning
confidence: 94%
“…Preparation of Nuclei and Core Particles and Protein-DNA Crosslinking Procedure-Nuclei from sea urchin sperm, chicken erythrocytes, mouse ascites, lily bud sepals, and yeast were isolated as described previously (17,18). Histone-DNA cross-linking, isolation of core particles, purification of cross-linked complexes, and two-dimensional gel electrophoresis of [ 32 P]DNA and 125 I-histone-labeled cross-linked complexes were performed as described (17,19).…”
Section: Methodsmentioning
confidence: 99%